Utilizing Monochlorinated Iodine as a Treatment for Trichophytosis in Cattle - Juraevna, Usmonova Khadicha (International Journal on Orange Technologies, 2023)
Trichophyton disease caused by Trichophyton verrucozum has been common among livestock in recent years. Monochlorinated iodine preparation consists of 3% and 30% hydrogen chloride and is used for aerosol disinfection and inhalation purposes. This tool is used as an ointment in the treatment of cattle trichophytosis.